Linguistic ethnography : collecting, analysing and presenting data - Copland, Fiona, 1962-; Creese, Angela; Rock, Frances, 1974-; Shaw, Sara. (Los Angeles : SAGE, 2015)
'This is an engaging interdisciplinary guide to the unique role of language within ethnography. The book provides a philosophical overview of the field alongside practical support for designing and developing your own linguistic ethnographic research. It demostrates how to build and develop arguments and engages with practical issues such as ethics, transcription and impact. There are chapter-long case studies based on empirical research that will explain key themes and help you collect and analyse your own linguistic data. Drawing on the author's experience, they outline the practical, epistemological and theoretical decisions that researchers must take when planning and carrying out their studies'--Back cover.
Part one. Ethnography and language -- Linguistic ethnography -- Data in linguistic ethnography -- Part two. Doing research in linguistic ethnography: building the case -- Case study one: reflexivity, voice and representation in linguistic ethnography (Angela Creese) -- Case study two: researching feedback conferences in pre-service teacher training (Fiona Copland) -- Case study three: ethnography and the workplace (Frances Rock) -- Case study four: ethnography, language and healthcare planning (Sara E. Shaw) -- Part three. Practical issues in linguistic ethnographic research -- Empiricism, ethics and impact -- Transcription, translation and technology -- Writing up: genres, writer voice, audience -- Ways forward.
Includes bibliographical references (pages 233-253) and index.
Keywords: Linguistics -- Research -- Methodology; Linguistics -- Research -- Methodology -- Case studies; Sociolinguistics; Sociolinguistics -- Case studies